Membangun Negara Indonesia Berdasar Nilai-Nilai Luhur yang terkandung di dalam Syair Lagu Kebangsaan Indonesia Raya - Akwan, Umbu Nusa Putra (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
This research aims to explore the noble values contained in the verses of the national anthem Indonesia Raya as a guideline in the development of the Indonesian nation. Through the approach of exegesis analysis and melodic movement, this study identifies the deep meaning in the lyrics of songs that have only been considered ceremonial symbols. The results of the study show that Indonesia Raya is not just a national anthem, but also contains a call for unity, struggle, and national development based on noble values. The phrase "Indonesia my homeland, the land of my blood" affirms a strong national identity, while the call "Let us call out, Indonesia is united" is a call to maintain harmony in the midst of the nation's diversity. Furthermore, the phrase "Build the soul, build the body" emphasizes that national development must be oriented towards strengthening the character and welfare of the people. The analysis of the melody shows the use of notation that describes the spirit of nationalism and the struggle in achieving independence and defending sovereignty. In conclusion, the poetry of Indonesia Raya contains basic principles in building a strong, independent, and sovereign nation. Therefore, the deep meaning of this national anthem is important for policy makers and the community in carrying out national development oriented towards social justice and people's welfare. This understanding is expected to strengthen the awareness of nationalism and build a stronger national unity.